Graves’ Disease and Diabetes Mellitus - Assin, M. Suttan; Rukman, Jusuf; Batubara, Jose R. L.; S. P., Purnama Wati (Paediatrica Indonesiana, 2019)
Thyroid hormones play an important role in the metabolic propesses. Its disturbances will involve several organs, consequently. A 5 year old girl with Graves’ diseases, after several weeks of treatment with propylthiouracil (PTV), developed thyrotoxicosis crisis and diabetes mellitus with ketoacidosis; a condition which is usually fatal. Treatment toward the hyperthyroid state overcome the diabetic stage, eventually. This report is an example of an endocrinological interaction in a hyperthyroid patient. Therefore, the diabetogenic effect of hyperthyroxinemia should not be overlooked.